Proceedings of the Conference on Water Waves: Theory and Experiment, Howard University, USA, 13-18 May 2008 - Mahmood, M. F.; Henderson, Diane; Segur, Harvey (World Scientific, 2010)
The objective of this book is to introduce new researchers to the rich dynamical system of water waves, and to show how (some) abstract mathematical concepts can be applied fruitfully in a practical physical problem and to make the connection between theory and experiment. It provides a coherent set of lectures on the current status of water wave theory, including identification of some open problems.